Pictographic and Pictorial: Street Art in Art History - Martinez, Elisa de Souza (Farol, 2025)
The public space of Brasília's Pilot Plan, created by Lucio Costa, is protected by heritage listing laws that guarantee the preservation of general formal principles in accordance with the modern project. The occupation of this listed space with works of art intensified from the 1980s onwards, when, in addition to works commissioned from modernist artists, the production of street art intensified. In the context of discussions about the end of originality and the unlimited expansion of the repertoire of techniques for creating open-air murals, different modes of occupying the city's walls emerged. Among these, this work distinguishes a group of panels with pictorial qualities, which link them to the field of art history.
Keywords: art in Brasília; street art; murals; artistic canon; modern heritage